Domains and outcomes of the core outcome set of congenital melanocytic naevi for clinical practice and research (the OCOMEN project): part 2. (14th July 2021) - Fledderus, A.C.; Pasmans, S.G.M.A.; Wolkerstorfer, A.; Oei, W.; Etchevers, H.C.; van Kessel, M.S.; van der Horst, C.M.A.M.; Spuls, P.I.
Abstract: Background: Congenital melanocytic naevi (CMN) can have a great impact on patients' lives owing to perceived stigmatization, and the risk of melanoma development and neurological complications. Development of a core outcome set (COS) for care and research in CMN will allow standard reporting of outcomes. This will enable comparison of outcomes, allowing professionals to offer advice about the best management options. In previous research, stakeholders (patients, parents and professionals) reached consensus on the core domains of the COS. To select the appropriate measurement instruments, the domains should be specified by outcomes. Objectives: To reach consensus on the specific core outcomes describing the core domains pertaining to clinical care and research in CMN. Methods: A list of provisional outcomes (obtained earlier) was critically reviewed by the Outcomes for COngenital MElanocytic Naevi (OCOMEN) research team and by relevant stakeholders through an online questionnaire, to refine this list and provide clear definitions for every outcome. When needed, discussion with individual participants was undertaken over the telephone or by email. During an online consensus meeting, stakeholders discussed the inclusion of potential outcomes. After the meeting, participants voted in two rounds for the inclusion of outcomes. Results: Forty‐four stakeholders from 19 countries participated. Nine core outcomes were included in the COS relative to clinical care and 10 core outcomes for research. Conclusions: These core outcomes will enable standard reporting in future care and research of CMN. This study facilitates the next step of COS development: selecting the appropriate measurement instruments for every outcome. Abstract : What is already known about this topic? Congenital melanocytic naevi (CMN) can be associated with psychosocial burden and increased risk of melanoma and/or neurological complications. Outcomes measured for research and care in CMN are heterogeneous, impeding comparison. A core outcome set (COS) may enhance standardized use and reporting, and reduce selective reporting bias. In previous research, relevant stakeholders reached consensus on what domains should be included in the core domain set (CDS). What does this study add? To select the appropriate measurement instruments for the domains included in the CDS, the domains should be further specified by outcomes. We reached consensus on what outcomes should describe the domains of the CDS of CMN care and research. Through a consensus procedure, including online discussions, online consensus meeting and voting, relevant stakeholders reached consensus on a limited number of core outcomes describing the core domains. What are the clinical implications of this work? Development of a COS will allow standard reporting of outcomes in future care and research of CMN. This will enable pooling and comparison of outcomes, allowing guideline development of optimal management policy. Linked Comment:  M.V. Heppt et al. Br J Dermatol 2021; 185:881–882 . Plain language summary available online